Facile air-oxidation of N-homopiperonyl-5,6-dimethoxyhomophthalimide: simple and efficient access to nuevamine - Wakchaure, Prasad B.; Easwar, Srinivasan; Puranik, Vedavati G.; N. P. Argade (Tetrahedron, 2008)
A facile six-step synthesis of naturally occurring (+/-)-nuevamine with 55% overall yield has been described, starting from methyl 2-(6-formyl-2,3-dimethoxyphenyl)acetate via the quantitative benzylic air-oxidation of the corresponding N-homopiperonyl-5,6-dimethoxy-homophthalimide to N-homopiperonyl-5,6-dimethoxyisoquinoline-1,3,4-trione as the key reaction, followed by base catalyzed regioselective alcoholysis of the trione with ring contraction, acid catalyzed dehydrative ring closure of the formed lactamol and decarboxylation pathway. (C) 2007 Elsevier Ltd. All rights reserved.

Facile biogenetic synthesis of pulcheotine A - Wakchaure, Prasad B.; N. P. Argade (Synthesis-Stuttgart, 2008)
Starting from homopiperonylamine and 4-methoxyphenylacetic acid, a facile biogenetic route to naturally occurring pulcheotine A has been demonstrated via Pictet-Spengler cyclization and two different air oxidation processes.
Keywords: 4-methoxyphenylacetic acid; homopiperonylamine; Pictet-Spengler cyclization; pulcheotine A; regioselective air oxidations

Green and sustainable approach to BIS-(INDOLYL) alkanes - Gholap, Somnath S.; Wakchaure, Prasad B.; Pandhare, Gajanan R.; Gill, Charansingh H. (Indian Journal of Heterocyclic Chemistry, 2009)
An efficient, high yielding, green and mild method has been developed for the synthesis of bis (indolyl) methanes using dodecylsulphonic acid as an effective surfactant type Bronsted acid catalyst in aq media. The method is excellent for various new bis-(indolyl) methanes derived from pyrazolaldehydes.

Stereoselective synthesis of (+)-isoindolo-beta-carboline - Wakchaure, Prasad B.; Puranik, Vedavati G.; N. P. Argade (Tetrahedron-Asymmetry, 2009)
Starting from homophthalic anhydride and (S)-tryptophan, the stereoselective synthesis of (+)-isoindolo-beta-carboline has been described via the corresponding homophthalimide, its chemoselective oxidative ring contraction, and the intramolecular dehydrative ring closure followed by a geometry-specific demethoxycarbonylation. (C) 2009 Elsevier Ltd. All rights reserved.

Synthesis of the reported protoberberine gusanlung D - Wakchaure, Prasad B.; Easwar, Srinivasan; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from homopiperonylamine or phenethylamine with homophthalic anhydride or 3,4-methylenedioxyhomophthalic acid, respectively, facile syntheses of the reported structures of (+/-)-gusanlung D and (+/-)-isogusanlung d were accomplished via regioselective reductive dehydration of the corresponding homophthalimides followed by an intramolecular acid-catalyzed or radical cyclization pathway. Starting from the corresponding suitably ortho-halogenated homophthalimides, the syntheses of dehydrogusanlung and dehydroisogusanhing D were completed via regioselective reductive dehydration followed by an intramolecular Heck coupling reaction as the key steps. The analytical and spectral data obtained for all four synthetic compounds differed from the reported data for natural gusanling D, and therefore the structural assignment of the natural product needs to be revised.
Keywords: gusanlung D; Heck reaction; homophthalic anhydride; homopiperonyl amine; reductive dehydration

Intramolecular chemoselective acylation of a suitably substituted isoindole: synthesis of (+/-)-chilenine and (+/-)-deoxychilenine - Wakchaure, Prasad B.; N. P. Argade (Synthesis-Stuttgart, 2011)
Starting from 3,4-dimethoxyhomophthalic anhydride and 6-bromohomopiperonylamine, concise and efficient syntheses of Chilean berberis products chilenine and deoxychilenine have been demonstrated via partially divergent routes by taking advantage of facile air-oxidation of homophthalimide along with intramolecular chemoselective acylation as the key steps.
Keywords: chemoselective acylation; chilenine; deoxychilenine; homophthalic anhydride; isoindole; Total synthesis

Regioselective NaBH4 and DIBAL-H reductions of 3,4-dimethoxyhomopiperonylphthalimide: concise and efficient synthesis of nuevamine and isonuevamine - Wakchaure, Prasad B.; Kunte, Sunita S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2011)
Facile synthesis of nuevamine and isonuevamine has been reported via the regioselectivc reduction of hindered and unhindered carbonyl groups of 3,4-dimethoxyhomopiperonylphthalimide, respectively using sodium borohydridc and diisobutylaluminum hydride, Mowed by an acid catalyzed intramolecular dehydrative cyclization pathways. The chemistry involved in obtaining the regioselectivity has been discussed in brief.
Keywords: 6-dimethoxyhomophthalimide; intramolecular dehydrative cyclizations; isonuevamine; N-Homopiperonyl-5; nuevamine; regioselective reductions; synthesis